New Horizons for Biocatalytic Science - Woodley, John M. (Frontiers in Catalysis, 2022)
The use of highly selective enzymes to catalyze value-added reactions outside the cell is commonly termed biocatalysis. In this brief perspective, some of the future opportunities for the application of biocatalysis are discussed. First, there are opportunities using multi-enzyme cascades where entirely new synthetic routes can be created independent of cellular constraints. Here the target is mostly high-priced products, such as pharmaceuticals. Secondly, there also exist opportunities for biocatalysis in the synthesis of low-priced products where the high productivities achievable make them eminently suited for drop-in solutions. Both options provide a wealth of interesting research and development possibilities, which are also discussed.